MARKETING MIX AS FACTORS IMPACT ON STUDENT’S ENROLLMENT IN PRIVATE HIGHER EDUCATION IN CAMBODIA - Phan, Sopisey; Hok, Thavuth; Long, Sovang (Srawung: Journal of Social Sciences and Humanities, 2025)
In contemporary contexts, marketing has emerged as a key element to contribute the success of private higher education (PHEs). The purpose of this research to explore the components of the Marketing mix and their impact on student’s enrollment in private higher education in Cambodia (PHEs). Various sampling techniques, including purposive, simple random, and quota sampling, were used in this quantitative study, resulting in a participant of 600 students enrolled in diverse majors across three universities, from their studies in year1 semester2 to year 4. In order to investigate the relationship between the components of the marketing mix and student’s enrollment, this research utilized adaptations of CFA (Confirmatory Factor Analysis) and SEM (Structural Equation Modeling). The results indicated a notable and positive connection between the components of product, price, promotional, people, and process with the rates of student’s enrollment. In contrast, the aspects of placement and physical evidence did not show any significant impact. The findings contribute to existing literature by offering insights rooted in buying behavior theory. Consequently, it is recommended that universities tailor their marketing strategies to align with their specific contexts, with an emphasis on optimizing pricing and promotional efforts to bolster their student recruitment endeavors based on their financial capacities.